Plasma Kynurenine-to-Tryptophan Ratio, a Highly Sensitive Blood-Based Diagnostic Tool for Tuberculosis in Pregnant Women Living With Human Immunodeficiency Virus (HIV). (15th March 2021) - Adu-Gyamfi, Clement; Savulescu, Dana; Mikhathani, Lillian; Otwombe, Kennedy; Salazar-Austin, Nicole; Chaisson, Richard; Martinson, Neil; George, Jaya; Suchard, Melinda
Abstract: Background: For pregnant women living with human immunodeficiency virus (HIV), concurrent active tuberculosis (TB) disease increases the risk of maternal mortality and poor pregnancy outcomes. Plasma indoleamine 2, 3-dioxygenase (IDO) activity measured by kynurenine-to-tryptophan (K/T) ratio has been proposed as a blood-based TB biomarker. We investigated whether plasma K/T ratio could be used to diagnose active TB among pregnant women with HIV. Methods: Using an enzyme-linked immunosorbent assay (ELISA), we measured K/T ratio in 72 pregnant women with and active TB and compared them to 117 pregnant women with HIB but without TB, matched by age and gestational age. Results: Plasma K/T ratio was significantly elevated during pregnancy compared to sampling done after pregnancy ( P < .0001). Pregnant women who had received isoniazid preventive therapy (IPT) before enrollment had decreased plasma K/T ratio compared to those who had not received IPT ( P = .0174). Plasma K/T ratio was elevated in women with active TB at time of diagnosis compared to those without TB ( P < .0001). Using a cutoff of 0.100, plasma K/T ratio gave a diagnostic sensitivity of 94% (95% confidence interval [CI]: 82–95), specificity of 90% (95% CI: 80–91), positive predictive value (PPV) 85% and negative predictive value (NPV) 98%. A receiver operating characteristic curve (ROC) gave an area under the curve of 0.95 (95% CI: .92–.97, P < .0001). In conclusion, plasma K/T ratio is a sensitive blood-based diagnostic test for active TB disease in pregnant women living with HIV. Plasma K/T ratio should be further evaluated as an initial TB diagnostic test to determine its impact on patient care. Abstract : There is an urgent need for a non-sputum-based tuberculosis test capable of detecting active tuberculosis. In this study, we show that plasma K/T ratio is a sensitive blood-based diagnostic test for active tuberculosis in pregnant women living with human immunodeficiency virus.